Effects of Caprylic Triglyceride on Cognitive Performance and Cerebral Glucose Metabolism in Mild Alzheimer’s Disease: A Single-Case Observation - Farah, Brian Andrew (Frontiers in Aging Neuroscience, 2014)
Objective: To examine the effect of 109 days of caprylic triglyceride (CT) in a 70 year-old male with mild Alzheimer’s disease (AD). Background: Cerebral metabolism is limited to glucose under most conditions, and diminished cerebral glucose metabolism is a characteristic feature of AD. Another substrate available for cerebral metabolism is ketone bodies. Ketone bodies are normally derived from fat stores under conditions of low glucose availability as an alternative energy substrate to glucose. Ketone bodies can also be produced by oral administration of CT. Prior studies suggest that the alternative energy source of CT may improve cognitive function due to mild to moderate AD, by circumventing the diminished glucose metabolism. Method: The effect of CT was analyzed in a single-case of mild AD with cognitive alterations in an open label study. Study outcomes included the Montreal Cognitive Assessment (MoCA), Mini Mental State Exam (MMSE) and 18-Fluorodeoxyglucose (18F) Positron Emission Tomography (FDG PET) scans. Results: After 109 days of CT, MoCA scores changed from a baseline value of 24 to 28, and MMSE scores changed from 23 to 28. No changes were observed on FDG PET scans. Conclusion: The results suggest that, in a case of mild AD, CT may have affected cognitive function, assessed by means of MMSE and MoCA, although glucose uptake and metabolism remained unchanged.